The Activities of Resettlement Centers and Medical and Food Assistance to Resettles in Siberia in 1861-1905 - D. N. Belyanin (Научный диалог)
The question of creating a system of resettlement centers in Siberia in the post-reform period is considered. General review of the historiography of the issue, made by the author showed lack of its study. Attention is paid to medical and food assistance to peasant migrants during the period of the Committee of the Siberian Railway in the late XIX - early XX centuries. The results of a comparative analysis of the conditions for the resettlement of peasants to Siberia before the organization of the Committee of the Siberian Railway and during its activity are presented. It is proved that the Committee of the Siberian Railway was able to significantly improve the conditions of peasant resettlement, to organize medical and food assistance to the peasants resettling in Siberia. The novelty of the study is determined by poor knowledge of the issue; the author comes to the conclusion about the social nature of state assistance to resettles. The relevance of the work is due to the need to use historical experience both in the field of state regulation of migration processes and in the field of state policy for the development of Siberia. The importance of research on this topic is determined, firstly, by the growth of migration processes dynamics in the modern world; secondly, the relevance of the task of strengthening Russian statehood in the Far Eastern region.